A novel histone acetylation-associated gene signature with prognostic value in Ewing sarcoma - Anshun Wu; Fayin Liu; Lei Zhou; Runyi Jiang; Shangjiang Yu; Zihuan Zhou; Qi Zhang; Qian Zhang; Dongjie Jiang; Shaohui He; Haifeng Wei (Discover Oncology)
Abstract Histone acetylation is an important epigenetic modification, modulating the development of many tumors. However, the functions of most histone acetylation-related genes (HARGs) and their prognostic values in Ewing sarcoma (EWS) remain unclear. The current study aimed to investigate the prognostic values and potential functions of HARGs in EWS. After collecting EWS patients with mRNA sequencing data from the Gene Expression Omnibus (GEO) database and a list of HARGs from previous studies, Cox regression and Least Absolute Shrinkage and Selection Operator (LASSO) regression were performed to construct a prognostic gene signature based on HARGs. Then, four HARGs (TAF4, ATF2, HDAC2 and OGA) composed a formula to calculate risk score for each patient in the training cohort. Based on median risk score, all patients were classified into low- and high-risk group, and patients with high-risk score had a poor survival outcome (p < 0.001). The 1-, 2-,3- and 5-year AUC (0.853, 0.886,0.909and 0.833, respectively) showed the good ability of this signature to predict the prognoses of EWS patients. In addition, distinct functional enrichment and immune-related pathways were also observed in two risk groups. All results were validated in an external cohort from two dataset in GEO database. Moreover, it was found that silencing HDAC2 expression in EWS cells significantly suppressed the cell viability and migration capability. In conclusion, this is the first study to detect the prognostic values of HARGs in EWS patients, further developing a good prognostic signature based on HARGs, and HDAC2 might be an oncogene in the development of EWS.